(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Submental intubation is a simple safe and useful technique for air way management during maxillofacial surgery when both nasal and oral tracheal intubation are deemed unsuitable. This technique offers an optimal operating field and an opportunity to check the dental occlusion. It avoids the need for tracheostomy and its consequent morbidity. We present a case of multiple facial fractures where we avoided tracheostomy by the use of submental endotracheal intubation. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19818 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 54-57